Exploring the Iranian Female Sandwich Generation's Experiences of Multigenerational Caregiving Under the COVID-19 Pandemic: A Qualitative Study Using Situational Analysis - Razieh Rayanpour; Majid Movahed Majd; Mohammad Taghi Iman; Darius Zifonun (Shahrekord University of Medical Sciences, 2022)
Background and aims: Although female family caregivers, especially those who belong to the sandwich generation, are at the forefront of the coronavirus disease (COVID-19) battle, little is known about their experiences. The purpose of this qualitative study was to explore the female sandwich generation's experiences of multigenerational caregiving under the COVID-19 pandemic in Shiraz located in the southwest of Iran. Methods: Situational analysis (SA) was used as a methodological approach. It is a constructivist grounded theory (GT) developed by Adele Clark as one of the innovative extensions of the GT. In the current study, the multigenerational caregiving by the female sandwich generation under the COVID-19 pandemic is identified as "the situation" which is the key unit of analysis and the salient and diverse elements of this situation (e.g., the major human, non-human, discursive, cultural, political, and other elements) were laid out by the messy and ordered maps. In addition, each element on the messy map was analyzed in relation to all other elements, and the nature of the relations among them was examined by the relational map. These maps are derived from qualitative data including the ethnographic observations, discourse materials, and in-depth semi-structured interviews with 10 middle-aged female double caregivers of both dependent children and the elderly above 70 years old within the family. Three sampling methods were used across the full trajectory of the research, including purposeful, snowball, and theoretical sampling. Results: The analysis of the multigenerational caregiving situation showed that this situation consists of 95 elements classified under 15 categories and 2 situational maps, along with 2 relational maps that have been drawn from the qualitative data analysis. Based on the organized situational map, this situation occurred as a result of the power of the main discourses, as well as the existing cultural, traditional, and religious elements, and continues after interconnecting to the global COVID-19 pandemic. The first relational map displayed caregivers' adopted information and communications technology (ICT) tool-based strategies such as remote caregiving, telehealth, online visiting, and online shopping, along with the voluntarily double quarantine in order to protect the elderly from COVID-19 infection. Finally, the second relational map depicted that emotional exhaustion is rampant among the caregivers influenced by the experiences that are related to the ICT tools and the voluntarily double quarantine. Conclusion: Overall, some strategies are suggested concerning the necessity of maintaining the mental and physical health of double caregivers and reduction of the negative consequences of the pandemic in them. They include accessibility of ICT tool-based strategies to all, the alternative approaches to severe social isolation, creation of a balance between work-home life and the care demands of two generations, early assessment of the psychological status along with the extensive support by the government, and formal care services to them.